2013
DOI: 10.1371/journal.pone.0081838
|View full text |Cite
|
Sign up to set email alerts
|

Protection Enhances Community and Habitat Stability: Evidence from a Mediterranean Marine Protected Area

Abstract: Rare evidences support that Marine Protected Areas (MPAs) enhance the stability of marine habitats and assemblages. Based on nine years of observation (2001–2009) inside and outside a well managed MPA, we assessed the potential of conservation and management actions to modify patterns of spatial and/or temporal variability of Posidonia oceanica meadows, the lower midlittoral and the shallow infralittoral rock assemblages. Significant differences in both temporal variations and spatial patterns were observed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 87 publications
6
48
0
Order By: Relevance
“…This evidence underlines the importance of MPAs for the conservation of this species. Until now, a positive 'reserve effect' has been observed mainly for the fish community (Francour 1994;La Mesa & Vacchi 1999;Guidetti 2006;Guidetti et al 2008;La Mesa et al 2011), while controversial data have been obtained for the invertebrate benthic assemblages (Lester et al 2009;Sala et al 2012;Fraschetti et al 2013). Our data are in agreement with the predictions of Linares et al (2010Linares et al ( , 2012 about the development of undisturbed red coral populations in MPAs of the NW Mediterranean Sea.…”
Section: Discussionsupporting
confidence: 88%
“…This evidence underlines the importance of MPAs for the conservation of this species. Until now, a positive 'reserve effect' has been observed mainly for the fish community (Francour 1994;La Mesa & Vacchi 1999;Guidetti 2006;Guidetti et al 2008;La Mesa et al 2011), while controversial data have been obtained for the invertebrate benthic assemblages (Lester et al 2009;Sala et al 2012;Fraschetti et al 2013). Our data are in agreement with the predictions of Linares et al (2010Linares et al ( , 2012 about the development of undisturbed red coral populations in MPAs of the NW Mediterranean Sea.…”
Section: Discussionsupporting
confidence: 88%
“…One reason for weaker and mixed outcomes in diversity is that not all species increase-and some decline-after reserve establishment (Micheli et al 2004b). As detailed in this section, community-level responses Variability in species diversity Decrease S: (Bates et al 2014) Variability/turnover in community assemblage/structure Lower S: (Fraschetti et al 2013, Mellin et al 2014, Wing & Jack 2013 Occurrence of nuisance species outbreaks Lower S: (McCook et al 2010) Resistance to disturbance Inconsistent or unaffected M: (Selig et al 2012, Worm et al 2006 Recovery rate Inconsistent or lower M: (Graham et al 2011, Worm et al 2006 Invasiveness Unaffected M: (Burfeind et al 2013, Guidetti et al 2014 a Increase can refer to a greater value (and decrease a smaller value) inside compared with outside reserves (more common) or after compared with before reserve establishment, depending on the study. b S, single study; M, meta-analysis, in which the response indicated is the cross-study average response, which might vary among studies.…”
Section: Community Consequences Of Marine Reservesmentioning
confidence: 99%
“…Several studies have documented the role of protection in enhancing the recovery trajectories of disturbed assemblages (Bellwood, Hughes, Folke, & Nyström, ; Bevilacqua et al, ; Micheli et al, ; Mumby et al, ), or in increasing their temporal stability (Fraschetti et al, ). However, despite the recognized importance of evaluating direct and indirect effects of protection in modifying patterns of spatial heterogeneity of marine assemblages (Benedetti‐Cecchi et al, ; Charton & Ruzafa, ), very few attempts have been made in this direction (Fraschetti, Guarnieri, Bevilacqua, Terlizzi, & Boero, ; Guarnieri et al, ).…”
Section: Introductionmentioning
confidence: 99%